Successful Endoscopic Submucosal Dissection Using Open Peroral Endoscopic Myotomy for Duodenal Neuroendocrine Tumor - Le, Ngoc Thi Bao; Park, Sang Jin; Cho, Bong Ju; Yang, Min A; Song, Jae Sun; Lee, Won Dong; Ju, Myoung Jin; Cho, Jin Woong (The Korean journal of gastroenterology, 2024)
Duodenal neuroendocrine tumors (NETs) are subepithelial tumors that are difficult to remove endoscopically, particularly when located just beyond the pylorus. This paper reports a case of a successful endoscopic submucosal dissection (ESD) using open gastric peroral endoscopic myotomy (POEM) for a remnant duodenal NET detected after endoscopic mucosal resection (EMR). A 67-year-old male presented with a 5 mm remnant duodenal NET close to the pylorus after EMR for a duodenal polypoid lesion performed four months earlier. Duodenal ESD was performed under conscious sedation using I-type and IT II knives. The tumor adhered to the fibrotic tissue, and the submucosal cushion was insufficient. Open gastric POEM was performed concurrently during ESD, resulting in the complete resection of the NET. This case suggests that while challenging, open gastric POEM can serve as a valuable technique for endoscopic resection in cases of early gastric cancer or duodenal masses located around the pylorus.